Implementation of the Supervisory Function in Improving Teacher Competence at Madrasah Aliyah Modern Pesantren IMMIM Putera Makassar - Rezeki, Sri; Malli, Rusli; Ali Bakri, Muhammad; Sumiati, Sumiati (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2024)
This study aims to explore the supervisory strategies employed by madrasah supervisors to enhance teacher competence at Madrasah Aliyah Pesantren Modern IMMIM Putera Makassar. Adopting a qualitative case study approach, the research provides a contextual analysis of academic and managerial supervision practices, as well as supporting programs such as workshops, teacher training, and classroom visits. Data were collected through in-depth interviews, participatory observation, and document analysis and were thematically analyzed to identify effective patterns, practices, and contributions to professional development. Findings reveal that academic supervision supports teachers in understanding student characteristics, designing contextual learning, and implementing innovative instructional models such as Discovery Learning and Project-Based Learning. Managerial supervision contributes to strengthening institutional governance through the digitalization of teaching documents, collaborative forums such as teacher working groups (MGMP), and consistent supervisory visits that enhance continuous monitoring and evaluation. Moreover, participatory development programs allow teachers to improve their pedagogical and professional competence within reflective and collaborative environments. The study underscores the importance of integrating structural and humanistic approaches in supervisory practices. The active involvement of supervisors in various forms of teacher development fosters a professional climate that supports sustained improvements in teaching quality and institutional performance. This research offers empirical insights to reinforce supervisory models based on contextual needs and provides a foundation for future policy development regarding teacher coaching in Islamic educational institutions.